2008
DOI: 10.1080/13697130701877108
|View full text |Cite
|
Sign up to set email alerts
|

Lipid levels and cardiovascular risk in elderly women: a general population study of the effects of hormonal treatment and lipid-lowering agents

Abstract: Objective: To evaluate plasmatic lipid levels in elderly women in the general population as a function of use of lipid lowering agents (LLA) and hormone therapy (HT) Methods: 4271 women over 65 were recruited from three French cities. Analyses were performed after stratification by LLA treatment and HT and adjusting for a large range of socio-demographic and clinical factors.Results: Fifteen percent of women currently used HT (78% transdermal estradiol), and 30% were taking LLA. In this population, 4.6% of wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This gender difference may be related to different hormonal status. Estrogen which could modify the cholesterol metabolic process was lower in postmenopausal women [39]. Animal study has suggested sex differences linked to a difference in LDL receptor [40].…”
Section: Discussionmentioning
confidence: 99%
“…This gender difference may be related to different hormonal status. Estrogen which could modify the cholesterol metabolic process was lower in postmenopausal women [39]. Animal study has suggested sex differences linked to a difference in LDL receptor [40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of dyslipidemia in primary care in France have either focused on LDL-C and/or TC2224 or have reported values for individual lipids (TC and triglycerides;25 LDL-C, HDL-C, and triglycerides26) according to NCEP ATP III guidelines 25,26. Studies of mixed dyslipidemias in European countries have applied NCEP ATP III guidelines27 or modified JES III guidelines 28.…”
Section: Introductionmentioning
confidence: 99%
“…LDL-C was determined by the Friedwald formula (22). Genotyping of ApoE and 5-HTTLPR was performed as described previously (23).…”
Section: Socio-demographic and Clinical Variablesmentioning
confidence: 99%